First contributions to the debate on China's Belt and Road Initiative in Latin America - Nagao Menezes, Daniel Francisco (Scientific journal of social studies, 2024)
When China invited Latin American countries to participate in the Belt and Road Initiative, it fueled expectations of a much closer and more productive relationship with the region. However, in practice, there is little evidence that this happened even before the coronavirus pandemic. The article shows that neither China’s policy statements nor trends in economic relations indicate a substantial change in Sino-Latin American relations and that the Belt and Road Initiative represents a rethinking of existing relations and the continuation of trends that have been underway since the global financial crisis.
Keywords: China; Latin America; Silk Road; Geopolitics